Weegy: x=-(2)/(3),2 is the answer...
3x^(2)-4x=4
To set the left-hand side of the equation equal to 0, move all the expressions to the left-hand side.
3x^(2)-4x-4=0..
Find the factors such that the product of the factors is the trinomial 3x^(2)-4x-4. [ This can be done by trial and error and checked using the FOIL method of simplifying polynomials.
(3x+2)(x-2)=0..
Set each of the factors of the left-hand side of the equation equal to 0.
3x+2=0_x-2=0...
Since 2 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 2 from both sides.
3x=-2_x-2=0...
Divide each term in the equation by 3.
(3x)/(3)=-(2)/(3)_x-2=0...
Simplify the left-hand side of the equation by canceling the common factors.
x=-(2)/(3)_x-2=0...
Set each of the factors of the left-hand side of the equation equal to 0.
x=-(2)/(3)_x-2=0...
Since -2 does not contain the variable to solve for, move it to the right-hand side of the equation by adding 2 to both sides.
x=-(2)/(3)_x=2...
The complete solution is the set of the individual solutions.
x=-(2)/(3),2.. ] OxTornado007|Points 6869|

There are no comments.